2010
DOI: 10.3763/ijas.2009.0481
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening capacity for sustainable livelihoods and food security through urban agriculture among HIV and AIDS affected households in Nakuru, Kenya

Abstract: The promotion and support of urban agriculture (UA) has the potential to contribute to efforts to address pressing challenges of poverty, under nutrition and sustainability among vulnerable populations in the growing cities of sub-Saharan Africa (SSA). This may be especially relevant for HIV/AIDS-affected individuals in SSA whose agricultural livelihoods are severely disrupted by the devastating effects of the disease on physical productivity and nutritional wellbeing. This paper outlines the process involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Researchers have begun to describe and evaluate integrated health and livelihood programs for PLHIV, mostly in rural settings in Africa, but much is unknown about optimal program and policy design (Gillespie & Kadiyala, 2005; Holmes, Winskell, Hennink, & Chidiac, 2011; Roopnaraine, Rawat, Babirye, Ochai, & Kadiyala, 2011; Samuels & Rutenberg, 2011; Yager, Kadiyala, & Weiser, 2011). Urban agriculture is being developed to strengthen capacity for sustainable livelihoods and food security among PLHIV in Kenya (Karanja et al, 2010), while urban farming among PLHIV in the U.S. has been proposed as a way to reduce psychological distress and social isolation and thereby reduce risk behaviors and improve chronic disease-related behaviors (Shacham et al, 2012). Although not specifically focused on PLHIV, another strategy in the U.S. to address food insecurity is via food rescue organizations, which obtain donations from farmers, manufacturers, wholesalers, supermarkets and restaurants (Hampl & Hall, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have begun to describe and evaluate integrated health and livelihood programs for PLHIV, mostly in rural settings in Africa, but much is unknown about optimal program and policy design (Gillespie & Kadiyala, 2005; Holmes, Winskell, Hennink, & Chidiac, 2011; Roopnaraine, Rawat, Babirye, Ochai, & Kadiyala, 2011; Samuels & Rutenberg, 2011; Yager, Kadiyala, & Weiser, 2011). Urban agriculture is being developed to strengthen capacity for sustainable livelihoods and food security among PLHIV in Kenya (Karanja et al, 2010), while urban farming among PLHIV in the U.S. has been proposed as a way to reduce psychological distress and social isolation and thereby reduce risk behaviors and improve chronic disease-related behaviors (Shacham et al, 2012). Although not specifically focused on PLHIV, another strategy in the U.S. to address food insecurity is via food rescue organizations, which obtain donations from farmers, manufacturers, wholesalers, supermarkets and restaurants (Hampl & Hall, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We defined women from 'HIVaffected' households as those whose households could be identified at baseline to have at least one adult member diagnosed with HIV through membership of a community-based organization for 'living positively' with assistance from a well-respected, community-based key informant (gatekeeper). We recruited the first 30 of these women by convenience from among the participants in a longitudinal follow-up assessment conducted by the authors on the effects of an urban agriculture intervention on infant and young child nutrition among HIV-affected households in Nakuru (the Sustainable Environments and Health Through Urban Agriculture, or SEHTUA project) (Karanja et al 2010). We recruited the remaining 45 of these women from community-based HIV/acquired immunodeficiency syndrome (AIDS) support/self-help groups using service-based convenience sampling.…”
Section: Group a ('Hiv-affected')mentioning
confidence: 99%
“…While this seems logical, and worth advocating, the evidence for increased urban agriculture as a response to HIVand AIDS at the household level is fragmentary. The examples from Zimbabwe cited by MDEPSA are all community or NGOled initiatives which, while important in their own right, do not relieve the need for further research to assess the possibilities and constraints on urban agriculture meeting the food and income needs of HIV-affected households (see Njenga et al 2009;Karanja et al 2010). AFSUN's regional survey found that only 20% of households in poor urban communities were growing any of their own food (Crush and Frayne 2010b).…”
Section: Reframing Hiv and Urban Food Securitymentioning
confidence: 98%